Photo Initiating System to Synthesize an Absorbent Hydrogel - Allam, Amr Emad El-Dien; Kamel, Shaimaa Ali (Majallat al-ʻimārah wa-al-funūn wa-al-ʻulūm al-insānīyah, 2019)
In order to synthesis absorbent hydrogel, Carboxy methylcellulose (CMC) was prepared by different DS. A superabsorbent hydrogel of carboxy methylcellulose (CMC) was initiated by UV system using methylenebisacrylamide (MBA) as a crosslinking agent and Photo initiator. For investigation the reaction of water absorbency of the hydrogels, the synthetic conditions were systematically optimized through studying the influential factors. The maximum water absorbency was achieved under the optimum condition of poly CMC that found to be CMC (DS 0.76) / 10 g, MBA = 0.5 gm, PI = 0.08 g, L.R 1:10, temp. 30  C and time 3 h.